ANTIOXIDANT AND FREE RADICAL SCAVENGING ACTIVITY OF HIBISCUS ACETOSELLA LEAVES EXTRACTS - DUMRONGPHUTTIDECHA, THISAKORN; THUNGMUNGMEE, SURADWADEE; KHOBJAI, WARACHATE; WISIDSRI, NAKUNTWALAI; TECHAEOI, SURACHAI (International Journal of Applied Pharmaceutics, 2019)
Objective: Hibiscus acetosella (HA) or Chaba Maple is native plant and cultivated in tropical western in Africa and north of America. The characteristics of HA are red to purple in stem, leaf, and flower that are the pigment of antioxidant compound as anthocyanins. Anthocyanins are in the group of flavonoid and have the role as functional foods which have several health benefits such as obesity and diabetes control, cardiovascular disease prevention, and others. Hence, the aim of this study was to investigate the antioxidant and free radical scavenging activity of HA leaves extracts. Materials and Methods: HA (Chaba Maple) leaves were collected in Pathum Thani province, Thailand, and were dried and extracted by maceration technique with three solvents – water, ethanol, and methanol. The antioxidant properties of extracts were carried out using 2,2’-azino-bis(3- ethylbenzothiazoline-6-sulfonic acid) (ABTS) radical scavenging assay and ferric reducing antioxidant power (FRAP) assay. The extracts were examined for their scavenging effect on hydroxyl radical (•OH) using hydroxyl radical scavenging assay and nitric oxide (NO) radical (•NO) using NO radical scavenging assay. Results: For ABTS, FRAP, and hydroxyl radical scavenging assay, ethanol extract showed the highest antioxidant property which the percentage inhibitions were 69.04%, 2381.84 μM/mg extract, and 62.88 mg/ml, respectively. For NO scavenging activity, methanol extract showed highest ability to scavenge NO which percentage inhibition was 101.28±0.73 mg/ml. Conclusion: The results of this study showed that ethanolic, methanolic, and water extract of HA leaves had scavenge and reducing antioxidant properties.